Outer surface protein (Osp) F subfamily antibody responses during Lyme disease - Werner, Ashley (My University, 2018)
Lyme disease is the most common tickborne illness in the United States. The CDC currently recommends a two-test system comprised of an enzyme linked immunosorbent assay followed by a Western blot for laboratory diagnosis. However, the approach is cumbersome and expensive, so identifying additional proteins that can be used to detect antibody responses associated exclusively with Lyme disease remains an important area of research. In this study, the genes encoding outer surface protein (Osp) F subfamily members OspF, OspEF-related protein G (ErpG), ErpK, and ErpL were cloned, and the resultant recombinant proteins were used to evaluate the antibody responses in wellcharacterized human Lyme disease sera. Although significant numbers of the Lyme disease sera contained antibodies that bound ErpG, ErpK, and/or ErpL, the responses were without an apparent pattern. In contrast, OspF antibodies were detected in a majority of patients with disseminated infection including 81% of patients with joint pain or swelling and each patient with cardiac abnormalities (3/3) or neuritis/neuropathy (2/2). Therefore, the findings failed to provide support for the diagnostic utility of the Erps, but additional studies to evaluate the utility of OspF for Lyme disease diagnostics are warranted.
Keywords: Lyme disease; Microbiology